Analisis Pengaruh Kepemimpinan dan Beban Kerja Terhadap Kepuasan Kerja pada Divisi Out Bond JNE Express Cabang Utama Medan - Gunawan, Mhd Fikri; Malikhah, Ikhah; Wakhyuni, Emi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine whether leadership and workload have a positive and significant simultaneous effect on job satisfaction of employees in the Out Bond Division of JNE Express Main Branch in Medan. The data analysis technique used is associative research method with the assistance of SPSS version 25. The type of research conducted is quantitative. The sample in this study consisted of 40 respondents. Primary data was collected using a questionnaire. The data analysis of the research used multiple linear regression analysis. The research results indicate that leadership has a positive and significant partial effect on employee job satisfaction in the Out Bond Division of JNE Express Main Branch in Medan. Workload has a positive and significant partial effect on employee job satisfaction in the Out Bond Division of JNE Express Main Branch in Medan. Leadership and workload have a positive and significant simultaneous effect on employee job satisfaction in the Out Bond Division of JNE Express Main Branch in Medan.